A rare case of cutaneous onchocerciasis in North-East India, review of literature - M M Pasha; Chetan C Patil; M Tanuja; Debdeep Mitra (Wolters Kluwer Medknow Publications, 2020)
Onchocerca volvulus is a spirurid nematode that mainly affects the rural poor of Sub-Saharan Africa, Yemen, and parts of Central and South America. River blindness caused by Onchocerca volvulus is considered to be the second most common infectious cause of blindness worldwide. We report a rare case of cutaneous Onchocerciasis from a non endemic area of North-East India. We could extract live adult worms from the subcutaneous lesions and also micro filariae from the skin nips. Onchocerca was confirmed based on its morphology. The patient has been subjected to therapy with ivermectin and doxycycline and is currently on regular follow up.